Analisis Potensi Kebangkrutan Berdasarkan Metode Altman Z – Score, Springate, dan Zmijewski pada Perusahaan Retail yang Terdaftar di Bursa Efek Indonesia Tahun 2015 – 2017 - Dian Andriani; Fredella Colline (Ilmiah Manajemen Bisnis, 2019)
Abstract — This research aims to analyze and measure the potensial of company bankruptcy using Altman Z-Score method, Springate, and Zmijewski. Bankruptcy level analysis is done to predict a company as a consideration of the condition of a company. The purpose of this study was to fnd out the potential bankruptcy rates in retail companies in 2015 – 2017. The sample uses 21 retail companies listed on the Indonesian Stock Exchange in 2015 – 2017. The method used in determining the sample is purposive sampling. The results of data processing using the three analytical methods obtained results that are different from each other, and there 2 companies that experience tend to go bankrupt in 2015 -2017 using the three methods.Keywords — Bankruptcy, Altman Z-Score, Springate,Zmijewski, Retail